Rute Terpendek Penyebaran Brosur dan Pemasaran Bimbel Himalaya dengan Nearest Neighbour Algorithm - Cynthia Alvionita Ferima (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
Bimbel Himalaya as one of the tutoring in Mojokerto City which has the potential as a place for teaching and learning activities between students and Tentor. In the city of Mojokerto there are many schools of all levels, namely Elementary Schools, Junior High Schools, and Senior High Schools. This research is limited to high school level. The design of this study to find travel routes in the distribution of brochures is very necessary in order to obtain the effectiveness of the minimum distance. In this connection, graph theory as a branch of mathematics is used to complete the design using the nearest neighbor algorithm method. The location of the Himalayan tutor is represented by a point and a connecting road between two locations is represented by a directed line. This study used a route model for Himalayan tutoring staff and 15 high schools in Mojokerto with a minimum distance.